The Educational Equity for Children of Long-term Inner Migrant Workers: case studies in Zhejiang Province, China - WU, Xin; Wang, Yu; Wang, Chenxi; Dai, Xiaoling; Xu, Zhengkai (MAJ - Malaysia Architectural Journal, 2025)
China's rapid urbanization and unbalanced regional developments has brought on not only population mobility of long-term inner migrant workers, but also the quality issue in their access to education and other resources for themselves and their family. Most of the current studies on educational equity for inner migrant children concentrate on finding ways to improve teaching and classroom performance from a pedagogical perspective, addressing institutional factors, such as entry barriers and educational policies. Little attention has been paid to non-institutional factors like urban and school environments, which have a greater impact on a long-term inner immigrant family's decision of their children's schooling. However, it is impossible to discuss non-institutional factors in a vacuum from institutional factors. The results of a mix method study using policy research, semi-structured interviews, questionnaires, and tracing indicated that childcare costs matter the most compare with other main categories of factors. Social feelings of children, family adherence, parental concerns about education quality, and the policies governing the care of talented and non-talented migrant workers in the workplace also significantly influenced migrant workers' willingness to migrate with their children. The study also discovered that there is no correlation between parents' education nor their desire to migrate. Furthermore, the discriminations in society against migrant workers is declining.